2021
DOI: 10.1242/jcs.256529
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of micron-scale protein-depleted plasma membrane domains in phosphatidylserine-deficient yeast cells

Abstract: Membrane phase separation to form micron-scale domains of lipids and proteins occurs in artificial membranes; however, a similar large-scale phase separation has not been reported in the plasma membrane of the living cells. We show here that a stable micron-scale protein-depleted region is generated in the plasma membrane of yeast mutants lacking phosphatidylserine at high temperatures. We named this region the ‘void zone’. Transmembrane proteins and certain peripheral membrane proteins and phospholipids are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 120 publications
(145 reference statements)
1
5
0
Order By: Relevance
“…ER-PM tethering is dynamically reorganized by changes in PM lipid composition and posttranslational modification–or Ca 2+ -dependent alteration of lipid-binding affinity of the tethering proteins ( 4 , 6 , 53 ). We revealed that PM-localized proteins, including the oligomerized PM-binding motifs of Ist2, were excluded from the bud sites, indicating that PM binding is crucial for the exclusion of ER-PM tethering proteins.…”
Section: Discussionmentioning
confidence: 99%
“…ER-PM tethering is dynamically reorganized by changes in PM lipid composition and posttranslational modification–or Ca 2+ -dependent alteration of lipid-binding affinity of the tethering proteins ( 4 , 6 , 53 ). We revealed that PM-localized proteins, including the oligomerized PM-binding motifs of Ist2, were excluded from the bud sites, indicating that PM binding is crucial for the exclusion of ER-PM tethering proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid-ordered membrane domains were observed for ER-mitochondria, ER-PM, and ER-lipid droplet contact sites ( King et al, 2020 ). Recently, it was observed that in phosphatidylserine-deficient yeast strain, a large sterol-rich ‘void’ zone can be formed on the PM ( Mioka et al, 2022 ). Vacuole-PM MCS is preferentially formed with the void zone, even though it is depleted of integral and peripheric membrane proteins ( Mioka et al, 2022 ).…”
Section: A Hypothesis Regarding Endoplasmic Reticulum Membrane Contac...mentioning
confidence: 99%
“…Recently, it was observed that in phosphatidylserine-deficient yeast strain, a large sterol-rich ‘void’ zone can be formed on the PM ( Mioka et al, 2022 ). Vacuole-PM MCS is preferentially formed with the void zone, even though it is depleted of integral and peripheric membrane proteins ( Mioka et al, 2022 ). According to the proposed model, it is likely that the unique lipid composition of the ER membrane at the MCS is a direct consequence of unique lipid composition of pre-existing ER microdomains that formed the initial basis for their formation.…”
Section: A Hypothesis Regarding Endoplasmic Reticulum Membrane Contac...mentioning
confidence: 99%
“…The loss of ER-PM contacts under certain conditions is also compensated by vacuole-PM contact site formation. It was recently discovered that the PM of living yeast cells forms micron-scale protein-depleted regions termed "void zones" [111]. These domains resemble the artificial, phase-separated regions seen in giant unilamellar vesicles and giant PM vesicles but are in fact maintained by cells in an energy-dependent manner.…”
Section: Mcss In Sphingolipid Metabolismmentioning
confidence: 99%
“…Void zones lack association with the cortical ER but instead form contact sites with the vacuole, possibly to prevent membrane integrity defects at the interface of the phase separation which is prone to high membrane permeability [112]. Because the formation of void zones at the PM depends on sphingolipid synthesis [111], void zone-vacuole contacts may be involved in regulating sphingolipid metabolism or organization of the PM.…”
Section: Mcss In Sphingolipid Metabolismmentioning
confidence: 99%